Eight Vignettes for Problem-Based Learning Faculty Development - Christopher O'Neal (Association of American Medical Colleges, 2015)
Abstract These eight vignettes describe common problems encountered by tutors leading problem-based learning (PBL) sessions in medical schools and other professional education settings. The vignettes were created in 2014 and were originally implemented in June 2014 at the David Geffen School of Medicine (DGSOM) at UCLA in response to issues with PBL tutor performance observed during routine weekly observations by faculty development staff. They are intended for use by faculty developers at other institutions who are interested in providing development to PBL tutors at their schools. The problems presented in each vignette are particularly relevant to PBL as it is practiced at DGSOM but should be easily modifiable to other small-group learning activities and other institutions. Each vignette is short and is intended to be read, discussed, and debriefed in approximately 10 minutes. This brevity is due to their original intended use as faculty development during the hour-long weekly case reviews used to educate tutors on the medicine and biology behind each of our PBL cases. Very little time is reserved in these sessions for pedagogy-focused faculty development, so interventions must, by necessity, be brief. Each vignette includes one or two questions intended to prompt discussion, as well as a resource sheet that includes relevant research and best practices. While changes in tutor behaviors are very difficult to assess, 100% of faculty participants agreed or strongly agreed with the following statements: "The PBL faculty development mini-vignettes have helped me to reflect on my teaching in PBL," "Ten minutes is enough time to read the vignette, talk with colleagues, and debrief the vignette," and "The time spent on discussing the faculty development mini-vignettes is time well-spent." Ninety-two percent of faculty agreed or strongly agreed with the following statements: "I have learned useful tips for teaching from my colleagues during the vignette discussions," and "The vignettes presented so far have been relevant to the challenges I face when leading PBL."